2011
DOI: 10.1002/pbc.23013
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine S‐methyltransferase (TPMT) polymorphisms in children with acute lymphoblastic leukemia, and the need for reduction or cessation of 6‐mercaptopurine doses during maintenance therapy: The Polish multicenter analysis

Abstract: The results indicate that TPMT genotype influences the safety and efficacy of ALL treatment and genotype information may therefore be useful for optimizing 6-MP therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…On the basis of population studies, three alleles account for more than 95% of the clinically relevant TPMT variants: TPMT *2, TPMT *3A, TPMT *3C and subjects who have absent or a reduced rate of enzyme activity than normal have higher circulating drug concentrations and are vulnerable to toxicity when the standard dosage is used. In single TPMT functional and non-functional allele carriers, the initial doses of AZA or 6-mercaptopurine should be reduced by 30-70%, whereas in homozygote non-functional allele carriers the doses of thiopurine drugs should be reduced 10-fold, or patients should receive alternative therapy (35). Therefore a simple test for TPMT genotypes can provide an important molecular biomarker that predicts drug response for hematological malignancies, autoimmune diseases, and organ transplantation (8, 41).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of population studies, three alleles account for more than 95% of the clinically relevant TPMT variants: TPMT *2, TPMT *3A, TPMT *3C and subjects who have absent or a reduced rate of enzyme activity than normal have higher circulating drug concentrations and are vulnerable to toxicity when the standard dosage is used. In single TPMT functional and non-functional allele carriers, the initial doses of AZA or 6-mercaptopurine should be reduced by 30-70%, whereas in homozygote non-functional allele carriers the doses of thiopurine drugs should be reduced 10-fold, or patients should receive alternative therapy (35). Therefore a simple test for TPMT genotypes can provide an important molecular biomarker that predicts drug response for hematological malignancies, autoimmune diseases, and organ transplantation (8, 41).…”
Section: Discussionmentioning
confidence: 99%
“…In western researches, both thiopurine S-methyltransferase (TPMT) and inosine triphosphate pyrophosphatase (ITPA) variant alleles have been reported to influence the need for 6-MP dose reduction or therapy interruption during maintenance therapy. [1][2][3][4] TPMT variant alleles are rare in the Japanese population, and even patients with wild-type TPMT alleles have shown severe toxicities that require therapy interruption or 6-MP dose reduction in Japanese. We have previously reported that patients with low ITPA activity frequently required therapeutic dose reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Those patients with TPMT*3A and TPMT*3C alleles required more frequent 6-MP dose reduction due to side effects such as anaemia and/or thrombocytopenia, leucopenia with respiratory tract infection. The results indicate that TPMT genotype influences the safety and efficacy of ALL treatment and genotype information may therefore be useful for optimizing 6-MP therapy [22]. De Jonge et al investigated the influence of polymorphisms of genes involved in folate metabolism on methotrexate sensitivity in vitro in 157 cases of paediatric ALL.…”
Section: Polymorphism In Drug Metabolising Genes and Treatment Responsementioning
confidence: 99%